AN ANALYSIS OF MORAL AND SOCIAL VALUES IN “RAYA AND THE LAST DRAGON” MOVIE - Anggreni Milenia Karo-Karo; Muhammad Kiki Wardana (Jurnal Scientia, 2022)
Film is a medium that is presented to entertain all people. Every film must have a moral message or values that always motivate the audience. In this study, the author analyzes the film entitled Raya and The Last Dragon which has moral and social values that can be learned by everyone, and aims to find out what types of moral values and social values are. This study uses descriptive qualitative theory with a grounded theory approach. The object of the research is a phenomenon that exists in its natural context and is understood after the field data is obtain, whether through interview or observation, interpreted. The result find that has a moral and social value in this movie, there are courage, honest, humble, patient, helping, wisdom, respect, work hard. This is a moral value that we must apply in order to become a person of good character.